Gene for susceptibility to diabetic nephropathy in type 2 diabetes maps to 18q22.3-23 - Vardarli, Irfan; Baier, Leslie J.; Hanson, Robert L.; Akkoyun, Imren; Fischer, Christine; Rohmeiss, Peter; Basci, Ali; Bartram, Claus R.; Woude, Fokko J. van der; Janssen, Bart (Kidney international, 2002)
BACKGROUND: Diabetic nephropathy is the major cause of end-stage renal failure in patients with diabetes mellitus types 1 and 2. Epidemiological studies have suggested a genetic susceptibility to diabetic nephropathy. The aim of this study was to localize the gene(s) responsible for susceptibility to diabetic nephropathy. METHODS: A genetic linkage analysis was performed in 18 large Turkish families with type 2 diabetes mellitus and diabetic nephropathy. The result was checked in 101 affected sibling pairs of Pima Indians. RESULTS: A highly significant LOD score of 6.1 on chromosome 18q22.3-23 between the markers D18S469 and D18S58 was obtained in multipoint analysis. There was no indication for locus heterogeneity. In Pima Indians, linkage to the markers D18S469 and D18S58 was confirmed (P = 0.033), using the affected sib-pair method. The genetic model that fit best was a dominant mode of inheritance with an almost complete penetration in the Turkish population. CONCLUSIONS: There is strong evidence for the localization of a gene responsible for diabetic nephropathy in Turkish type 2 diabetes mellitus patients. This locus maps to chromosome 18q22.3-23, between D18S43 and D18S50, an interval of 8.5 cM.
Online publiziert: 1 December 2002
Gesehen am 14.06.2022